EFFECT OF NITROGEN AND KINETIN ON THE GROWTH OF PLUM SEEDLINGS - Adil Khidir Al-Rawi (Mesopotamia Journal of Agriculture)
This experiment was conducted out Nineveh research station during 2001-2002 season to study the effect of four levels of nitrogen fertilizer (0, 10, 20 and 30kg N/donum) and four concentrations of kinetin (0, 50, 100 and 150 ppm) and their interaction on the growth of one year old of plum (Prunus myroblane Ehrh.) seedlings. A factorial experiment with three replications was carried out in a randomized complete block design (RCBD), each replicate was consist of 30 seedlings. Data Obtained of this research was tested by using Duncan Multiple range test at 5% level, the important results of this study could be summarized as following: The Most of nitrogen fertilizer treatments significant increase all characters of the vegetative and root growth of the plum seedlings (stem length, stem diameters, dry weight of vegetative system) and roots, leaves contents of nitrogen and Chlorophyll. The addition of kinetin treatments as caused a significant increase in stem diameter, nitrogen concentration in the leaves and total chlorophyll, but there is no significant increases in stem length, dry weigh of vegetative growth and roots. The interaction treatments between nitrogen and kinetin affected significantly in most of the vegetative characters of the growth, dry weight of roots, nitrogen content in leaves, total chlorophyll concentration of leaves. The best treatments was 30kg N/donum + zero mg/L kinetin in stem length 30kg N/donum + 190 mg/L kinetin in stem diameter, nitrogen concentration in leaves total chlorophyll content ,30Kg N/donum + 100 mg/L kinetin in dry weight vegetative growth .